Review Artikel : Potensi Berbagai Bahan Alam Sebagai Insektisida Alami Kutu Rambut (Pediculus humanus capitis) - Rifani Shalsadila; Mega Nuryanti; Purwaeni Purwaeni (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The head louse parasite (pediculus humanus capitis) is the cause of a common infection in tropical climates called pediculosis capitis. The food of head lice comes from the blood sucked on the human scalp. Various ways to deal with head lice are using lice combs and insect repellents (insecticides). Insecticidal liquid is a synthetic chemical containing permethrin, lindae, DDT malathion and carbaryl which can interfere with the human nervous system when used long-term. This study aimed to find various natural ingredients that have the potential as natural insecticides in overcoming pediculosis capitis. The method used was literature review through Google Scholar, ScienceDirect and ResearchGate websites. The results obtained are lime (Citrus hystrix), red betel (Piper ornatum), crimson (Annona squamosa), kirinyuh (Chromolaena adorate), pandan wangi (Pandanus amaryllifolius), bay leaves koja (Murraya koenigii L.), duku (Lansium domesticum corr), soursop (Annona muricata L.), eucalyptus (Melaleucalucalus L.), eucalyptus (Melaleuca cajuputi), garlic, shallots, coconut (Cocos nucifera), sembung rambat (Mikania micrantha), aloe vera (Aloe vera), jarak pagar (Jatropa curcas L.) and mengkudu (Morinda citrifolia) have the potential as natural insecticides in overcoming pediculosis capitis.